In vitro Characterization of Bacteriocin Produced by Lactic Acid Bacteria Isolated from Nem Chua, a Traditional Vietnamese Fermented Pork - Komkhae Pilasombut; Kittaporn Rumjuankiat; Nualphan Ngamyeesoon; Le Nguyen Doan Duy (My University, 2015)
The aim of this study was to screen and In vitro characterize the properties of bacteriocin produced by lactic acid bacteria isolated from Vietnamese fermented pork (Nem chua). One hundred and fifty LAB were isolated from ten samples of Nem chua and screened for bacteriocin-producing lactic acid bacteria. Antimicrobial activity of bacteriocin was carried out by spot on lawn method against both gram positive and gram negative bacteria. One isolate, assigned as KL-1, produced bacteriocin and showed inhibitory activity against Lactobacillus sakei, Leuconostoc mesenteroides and Enterococcus faecalis. To characterize the bacteriocin-producing strain, optimum temperature, incubation period for maximum bacteriocin production and identification of bacteriocin-producing strain were determined. It was found that the optimum cultivation temperature of the strain to produce the maximum bacteriocin activity (12,800 AU/mL) was obtained at 30℃. Meanwhile, bacteriocin production at 6,400 AU/mL was found when culturing the strain at 37℃ and 42℃. The isolate KL-1 was identified as L. plantarum. Antimicrobial activity of cell-free supernatant was completely inhibited by proteolytic enzyme of trypsin, alpha-chymotrypsin and proteinase K. Bacteriocin activity was stable at high temperature up to 100℃ for 10 min and at 4℃ storage for 2 d. However, the longer heating at 100℃ and 4℃ storage, its activity was reduced.
Keywords: Proteolytic enzymes; Lactobacillus sakei; Strain (injury); Probiotics and Fermented Foods